STUDENTS’ PERCEPTIONS OF THE USE OF GROUP WORK ACTIVITIES IN LEARNING ENGLISH - Suci Candrawinata; Chairil Anwar Korompot; Fitri Radhiyani (International Journal of Business English and Communication, 2025)
This research is descriptive qualitative research that aims to know students' perceptions of the use of group work activities in learning English. Group work activities serve as the independent variable, and students' perceptions, divided into cognitive, affective, and conative components, are the dependent variables. The population of this research is all ninth-grade students of SMP Negeri 3 Barru in the 2024/2025 academic year. The subjects of this research are students of class IX.1 SMP Negeri 3 Barru in the 2024/2025 academic year. The data for the research was obtained through interviews. The results showed that students' perceptions of group work activities in learning English were positive across all three components, highlighting its effectiveness in improving students' understanding, motivation, and participation in the learning process.